Hospital competition and quality with regulated prices - Kurt R. Brekke; Luigi Siciliani; Odd Rune Straume (Center for Economic Studies and ifo Institute (CESifo), 2009)
We analyse the effect of competition on quality in hospital markets with regulated prices, considering both the effect of (i) introducing competition (monopoly versus competition) and (ii) increasing competition through lower transportation costs (increased substitutability) or a higher number of hospitals. With semi-altruistic providers and a fairly general cost structure, we show that the relationship between competition and quality is generally ambiguous. In contrast to the received theoretical literature, this is consistent with, and potentially explains, the mixed empirical evidence.
Keywords: H42; I11; I18; L13; 330; hospitals; competition; quality; Krankenhaus; Dienstleistungsqualität; Nichtpreiswettbewerb; Unvollkommener Markt; Theorie